(untitled) (Eurasian Journal of Media and Communications, 2023)
Many countries have focused on handicrafts in their development programs to increase tourism demand. Tourist spending on handicrafts represents part of the total spending in the host country, as there is an interrelation between tourism and handicrafts. A group of tourists were surveyed about their opinions regarding the importance of the role of the tour guide in revitalizing handicrafts. The study sample was 40, and their views were measured statistically to reach the study objectives